Chloroplast redox metabolism and npq regulation in arabidopsis and rice exposed to excessive light - Carvalho, Fabrício Eulálio Leite (2016)
CARVALHO, Fabrício Eulálio Leite. Chloroplast redox metabolism and npq regulation in arabidopsis and rice exposed to excessive light: new insights into psii photoprotection mechanisms. 2016. 171 f. Tese (Doutorado em Bioquímica)-Universidade Federal do Ceará, Fortaleza, 2016.